2005
DOI: 10.2527/2005.8371526x
|View full text |Cite
|
Sign up to set email alerts
|

Carcass composition, bone mechanical properties, and meat quality traits in relation to growth rate in rabbits1

Abstract: The objective of this study was to characterize correlated responses in carcass composition, bone mechanical properties, and meat quality indicators to divergent selection for growth rate. Rabbits from low (LOW) or high (HIGH) lines divergently selected over five generations on 63-d BW and a control group (CONT) were used. Rabbits were slaughtered at an average BW of 2,306 +/- 65 g, corresponding to 63, 58, or 52 d of age in LOW (n = 41), CONT (n = 43), and HIGH (n = 44) groups, respectively. Postweaning ADG a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
0
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 27 publications
7
32
0
8
Order By: Relevance
“…Cryopreservation of mammalian embryos has benefitted both breeding and biomedical research in recent decades, due in part to the improvement of techniques related to vitrification, freezing-thawing processes, and transfer procedures. To this end, rabbit embryo banking has allowed the preservation and spread of genetically superior animals over different countries [34] and the possibility of evaluating the genetic gain in maternal lines [4][5][6][7] without cumulative genetic drift variance [35]. Nevertheless, it is known that these techniques induce changes in environ-mental and maternal side effects modifying the embryo gene expression and methylation pattern [19,20,36], the transcriptomic and proteomic placental profile [21], and their viability [29,37], but little is known regarding the long-term effects on the derived progeny.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryopreservation of mammalian embryos has benefitted both breeding and biomedical research in recent decades, due in part to the improvement of techniques related to vitrification, freezing-thawing processes, and transfer procedures. To this end, rabbit embryo banking has allowed the preservation and spread of genetically superior animals over different countries [34] and the possibility of evaluating the genetic gain in maternal lines [4][5][6][7] without cumulative genetic drift variance [35]. Nevertheless, it is known that these techniques induce changes in environ-mental and maternal side effects modifying the embryo gene expression and methylation pattern [19,20,36], the transcriptomic and proteomic placental profile [21], and their viability [29,37], but little is known regarding the long-term effects on the derived progeny.…”
Section: Discussionmentioning
confidence: 99%
“…Strain rederivation from cryopreserved embryos has been used to assess the genetic improvement of quantitative traits such as prenatal survival, litter size, and growth characteristics in polytocous species such as mice, rats, and rabbits [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Third, selection for loin depth may be acting through hormonal drivers of bone growth such as growth hormone (GH), since sheep expressing excess GH show increased bone growth yet relative under-muscling (Adams et al 2006), the opposite to that observed in the PD m × M genotype in the present study. Alternatively, a more prosaic explanation is that selection for PEMD EBV, which is referenced to bodyweight (Hall et al 2002) may inadvertently produce selection pressure for lighter appendages thus shorter limbs, as has been shown in other production animals such as rabbits (Gondret et al 2005) and broiler chickens (Reddish and Lilburn 2004). However, other data from this study demonstrating shorter carcass length in PD m × M compared with PD g × M animals (Ponnampalam et al 2007a), suggest that limb shortness is indicative of more generalised skeletal hypotrophy in this genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Selection for growth rate in rabbits has resulted in myofiber hypertrophy (Gondret et al, 2002), together with increased (Pascual and Pla, 2007) or unchanged (Hernandez et al, 2004) oxidative traits evaluated through enzymatic activity. Although a lower proportion of slow-type myosin heavy chain has been demonstrated in rabbits selected for a rapid growth rate (Ramírez et al, 2004), no changes in the relative proportion of fiber types as evaluated by m-ATPase histochemistry have been elicited (Gondret et al, 2005).…”
Section: Introductionmentioning
confidence: 99%